SIMULTANEOUS DETERMINATION OF PARACETAMOL AND IBUPROFENE MIXTURES BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Sophi Damayanti; Slamet Ibrahim; Kurnia Firman; Daryono H Tjahjono (Universitas Gadjah Mada, 2003)
Analytical method for the determination of paracetamol and ibuprofene mixtures has been developed by High Performance Liquid Chromatography using C-18 column and acetinitrile - phosphate buffer pH = 4.5 (75:25) containing 0.075% sodium hexanesulfunate as a mobile phase. The detector was set at 215 nm. Using such conditions, retention time for paracetamol and ibuprofen was 4.89 and 7.11 min, respectively. The recovery for paracetamol and ibuprofen was found to be 101.07± 0.73% and 102.02 ± 1.58%, respectively. The detector limits of the method was 1.30 and 1.60 μg/mL with the relative standard deviation (RSD) 0.74 and 1.52% for paracetamol and ibuprofen, respectively.